Effectiveness of Copper-Based Active Ingredients Against Bacterial Leaf Blight (Xanthomonas oryzae pv. oryzae) in Rice Plants - Hanif, Luthfan; Abadi, Abdul Latief (Journal of Tropical Plant Protection, 2024)
Rice is one of the food crops that is a basic need for the people of Indonesia, but rice production in Indonesia is unstable every year because of various factors, one of which is plant diseases, such as Bacterial Leaf Blight (BLB) caused by Xanthomonas oryzae pv. oryzae bacteria. Active ingredients that can be used to control bacteria are copper-based active ingredients. In addition, increasing the concentration or adding surfactant in pesticide formulations can increase the effectiveness of active ingredients. This research was conducted at the Plant Disease Laboratory, Plant Pests and Diseases Department, Faculty of Agriculture, Universitas Brawijaya and Ketangi Hamlet, Tegalgondo Village, Karangploso District, Malang Regency. The In Vitro research design used a complete randomized design (CRD) and the In Vivo used a randomized complete block design (RCBD)consisting of 7 treatments and 4 replications. The parameters observed were inhibition, intensity of BLB, phytotoxicity, yield, and efficacy level. The results showed that treating copper oxide 60 WP+Surfactant, copper oxide 60 WP, copper hydroxide 80 WP+Surfactant, and copper hydroxide 80 WP effectively controlled bacterial leaf blight. While the treatment of copper oxide Zn 60 WP and copper oxy sulfate 345 SC was ineffective in controlling BLB. Each treatment of copper-based active ingredients at a dose of 2 grams and 2 mL did not show symptoms of phytotoxicity.